The effectiveness of guided inquiry learning based on Anderson’s sketch analysis on students’ higher order thinking skills in reaction rate - Herunata, Herunata; Ibnatullatiefah, Ibnatullatiefah; Habiddin, Habiddin; Widarti, Hayuni Retno; Munzil, Munzil; Fauziah, Putri Nanda (Eclética Química, 2025)
The 21st century learning process focuses on enhancing higher-order thinking skills (HOTs). In Indonesian schools, students’ HOTs in the reaction rate topic need improvement. This study investigates the effectiveness of guided inquiry learning based on Anderson’s learning sketch analysis in enhancing HOTs. Involving 60 of 11th grade science students from a public high school in Malang, the study used a quasi-experimental design with an experimental class (Anderson’s learning sketch) and a control class (conventional learning). The research instrument was a HOTs assessment with 10 essay questions. Data analysis using an independent sample t-test showed a significant difference (p = 0.002), with the experimental class scoring higher (69.3) than the control class (49.9). The findings indicate that Anderson’s Learning Sketch Analysis is effective in improving students’ HOTs, with the experimental class outperforming the control class in skills such as analysis (63% vs. 39%), evaluation (71% vs. 55%), and creation (78% vs. 70%). These results highlight the importance of guided inquiry in enhancing HOTs.